Mixed-integer nonlinear programming for aircraft conflict avoidance by sequentially applying velocity and heading angle changes - Cafieri, Sonia; Omheni, Riadh (European journal of operational research, 2017)
•An emerging application of Operations Research arising in Air Traffic Management is considered.•A new MINLP formulation for aircraft conflict avoidance is proposed.•A two-step approach is proposed based on sequentially applying heading and speed changes.•Numerical experiments clearly show the benefit of the proposed methodological approach. We consider the problem of aircraft conflict avoidance in Air Traffic Management systems. Given an initial configuration of a number of aircraft sharing the same airspace, the main goal of conflict avoidance is to guarantee that a minimum safety distance between each pair of aircraft is always respected during their flights. We consider aircraft separation achieved by heading angle deviations, and propose a mixed 0–1 nonlinear optimization model, that is then combined with another one which is based on aircraft speed regulation. A two-step solution approach is proposed, where the two models are sequentially solved using a state-of-the-art mixed-integer nonlinear programming solver. Numerical results validate the proposed approach and clearly show the benefit of combining the two considered separation maneuvers.